3
$\begingroup$

I have the following sequence given:

$$\sum_{k=1}^{n} (-1)^{k}k^{2}$$

How can I do this? The sequence goes like this:

$$-1 + 4 - 9 + 16 - 25 + 36 - ...$$

So it doesn't have any variables inside. It looks like a geometric sequence for me, so the simple known formula would do the whole thing, but I actually doubt it's that simple.

So there are some generating functions that are quite similar, like:

$$\sum (-1)^{n}x^{n} = x - x^{2} + x^{3} - x^{4} + ...$$

But, uhm, well...what's next? The lack of x variable seems a bit strange to me.

$\endgroup$
0
2
$\begingroup$

Note that the generating function for the sequence $(-1)^k$ is $\frac{1}{1+x}$. Also observe that if $(a_k)$ is any sequence with generating function $f$, then the generating function for the sequence $(ka_k)$ is $x\frac{d}{dx} f$ and the generating function for the sequence $\sum a_k$ is $\frac{f}{1-x}$. With this in mind, we find the generating function for the sequence $(-1)^k k$ to be $$x\frac{d}{dx}\frac{1}{1+x}=-\frac{x}{(1+x)^2}$$ and so the generating function for $(-1)^k k^2$ is $$-x\frac{d}{dx}\frac{x}{(1+x)^2}=-\frac{(1-x)x}{(1+x)^3}$$

Thus, your generating function is $$-\frac{x}{(1+x)^3}$$

If we use partial fractions, we can write this as $$\frac{1}{(1+x)^3}-\frac{1}{(1+x)^2}$$ If we use the formla $$\frac1{(1+x)^k}=\sum_{n\ge 0}\binom{n+k-1}{k-1}(-x)^n$$ we finally get that the sum is $$\sum_{k=1}^n(-1)^k k^2=(-1)^n\left(\binom{n+2}{2}-\binom{n+1}{1}\right)$$

Edit: \begin{align} \frac{f}{1-x}&=\frac{1}{1-x}\sum_{k=0}^{\infty}a_kx^k=(1+x+...)\sum_{k=0}^{\infty}a_kx^k=\\ &=a_0+(a_0+a_1)x+(a_0+a_1+a_2)x^2+...= \\ &=\sum_{k=0}^\infty \left( \sum_{n=0}^k a_n\right)x^k \end{align}

$\endgroup$
4
  • 1
    $\begingroup$ It might be helpful to explain why you divided by $1-x$ to get the generating function. $\endgroup$ – robjohn May 11 '13 at 14:38
  • $\begingroup$ @robjohn Your wish is my command. $\endgroup$ – user60725 May 11 '13 at 16:08
  • 1
    $\begingroup$ The effect of $x\frac{\mathrm{d}}{\mathrm{d}x}$ on a generating function is pretty simple, but the effect of dividing by $1-x$ is not. I was thinking of something more like this: If $$ f(x)=\sum_{k=0}^\infty a_kx^k $$ then $$ \begin{align} \sum_{n=0}^\infty\left(\sum_{k=0}^na_k\right)x^n &=\sum_{k=0}^\infty\sum_{n=k}^\infty a_kx^n\\ &=\sum_{k=0}^\infty a_k\frac{x^k}{1-x}\\ &=\frac{f(x)}{1-x} \end{align} $$ $\endgroup$ – robjohn May 11 '13 at 16:42
  • 1
    $\begingroup$ Your final expression simplifies to$$(-1)^n \left(\binom{n + 2}{2} - \binom{n + 1}{1} \right) =(-1)^n \left( \frac{(n + 2) (n + 1)}{2} - \frac{n + 1}{1} \right) = \frac{(-1)^n n(n + 1)}{2}$$ $\endgroup$ – vonbrand May 15 '13 at 15:57
1
$\begingroup$

The generating function is $$ \begin{align} \sum_{n=0}^\infty\sum_{k=0}^n(-1)^kk^2x^n &=\sum_{k=0}^\infty\sum_{n=k}^\infty(-1)^kk^2x^n\\ &=\sum_{k=0}^\infty(-1)^kk^2\frac{x^k}{1-x}\\ &=\frac1{1-x}\sum_{k=0}^\infty(-1)^kk^2x^k\tag{1} \end{align} $$ Starting with $\frac1{1+x}$ and taking derivatives, we get $$ \begin{align} \frac1{1+x}&=\sum_{k=0}^\infty(-1)^kx^k\\ \frac1{(1+x)^2}&=\sum_{k=0}^\infty(-1)^k(k+1)x^k\\ \frac2{(1+x)^3}&=\sum_{k=0}^\infty(-1)^k(k+2)(k+1)x^k \end{align}\tag{2} $$ Since $k^2=(k+2)(k+1)-3(k+1)+1$, we have $$ \begin{align} \sum_{k=0}^\infty(-1)^kk^2x^k &=\frac2{(1+x)^3}-\frac3{(1+x)^2}+\frac1{1+x}\\ &=\frac{(x-1)x}{(1+x)^3}\tag{3} \end{align} $$ Thus, the generating function we want is $$ \begin{align} \frac1{1-x}\sum_{k=0}^\infty(-1)^kk^2x^k &=\frac1{1-x}\frac{(x-1)x}{(1+x)^3}\\ &=-\frac{x}{(1+x)^3}\\ &=-\sum_{n=0}^\infty\binom{-3}{n-1}x^n\\ &=\sum_{n=0}^\infty(-1)^n\binom{n+1}{n-1}x^n\\ &=\sum_{n=0}^\infty(-1)^n\binom{n+1}{2}x^n\tag{4} \end{align} $$ Therefore, $$ \sum_{k=0}^n(-1)^kk^2=(-1)^n\binom{n+1}{2}\tag{5} $$

$\endgroup$
0
$\begingroup$

Start with: $$ \sum_{0 \le k \le n} (-1)^k z^k = \frac{1 - (-z)^{n + 1}}{1 - (-z)} $$ Then note that: $$ z \frac{d}{dz} \sum_{k} a_k z^k = \sum_k k a_k z^k $$ This hints at differentiating the above sum twice and evaluating at $z = 1$: $$ z \frac{d}{dz} \left(z \frac{d}{dz} \frac{1 - (-z)^{n + 1}}{1 + z} \right) \big\lvert_{z = 1} = \frac{(-1)^n n (n + 1)}{2} $$

Maxima help with the mess is gratefully acknowledged.

$\endgroup$
0
$\begingroup$

The lazy (meaning: professional) way of getting the result is to generate the first few terms of the partial alternating sum, -1, 3, -6, 10, -15,.. and then to look up the terms in the http://oeis.org, leading to http://oeis.org/A089594, and take the g.f. from the formula section.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.